Future drought risk in Africa: Integrating vulnerability, climate change, and population growth - Ahmadalipour, Ali; Moradkhani, Hamid; Castelletti, Andrea; Magliocca, Nicholas (The Science of the total environment, 2019)
Drought risk refers to the potential losses from hazard imposed by a drought event, and it is generally characterized as a function of vulnerability, hazard, and exposure. In this study, drought risk is assessed at a national level across Africa, and the impacts of climate change, population growth, and socioeconomic vulnerabilities on drought risk are investigated. A rigorous framework is implemented to quantify drought vulnerability considering various sectors including economy, energy and infrastructure, health, land use, society, and water resources. Multi-model and multi-scenario analyses are employed to quantify drought hazard using an ensemble of 10 regional climate models and a multi-scalar drought index. Drought risk is then assessed in each country for 2 climate emission pathways (RCP4.5 and RCP8.5), 3 population scenarios, and 3 vulnerability scenarios during three future periods between 2010 and 2100. Drought risk ratio is quantified, and the role of each component (i.e. hazard, vulnerability, and exposure) is identified, and the associated uncertainties are also characterized. Results show that drought risk is expected to increase in future across Africa with varied rates for different models and scenarios. Although northern African countries indicate aggravating drought hazard, drought risk ratio is found to be highest in central African countries as a consequent of vulnerability and population rise in that region. Results indicate that if no climate change adaptation is implemented, unprecedented drought hazard and risk will occur decades earlier. In addition, controlling population growth is found to be imperative for mitigating drought risk in Africa (even more effective than climate change mitigation), as it improves socioeconomic vulnerability and reduces potential exposure to drought. [Display omitted] •Drought risk is studied in Africa by integrating hazard, vulnerability and exposure.•Multi-model and multi-scenarios are employed at a national level.•Uncertainty of each risk component is characterized for each country.•The role of climate change, population growth and vulnerability on risk is explored.•The spatiotemporal patterns of drought risk and its uncertainties are identified.